How solidarity works for welfare : subnationalism and social development in India - Singh, Prerna (Cambridge studies in comparative politics)
"Why are some places in the world characterized by better social service provision and welfare outcomes than others? In a world in which millions of people, particularly in developing countries, continue to lead lives plagued by illiteracy and ill-health, understanding the conditions that promote social welfare is of critical importance to political scientists and policy makers alike. Drawing on a multi-method study, from the late nineteenth century to the present, of the stark variations in educational and health outcomes within a large, federal, multiethnic developing country - India - this book develops an argument for the power of collective identity as an impetus for state prioritization of social welfare. Such an argument not only marks an important break from the dominant negative perceptions of identity politics but also presents a novel theoretical framework to understand welfare provision"--